Social norms and plastic avoidance: Testing the theory of normative social behaviour on an environmental behaviour. Issue 6 (21st June 2020) - Borg, Kim; Curtis, Jim; Lindsay, Jo
Abstract: Plastic pollution is a critical global sustainability challenge, but the social norms associated with single‐use plastics are changing. These new norms could be encouraging consumer behaviour change by highlighting which behaviours are common and acceptable. This paper explores the role of social norms in predicting plastic avoidance, using the theory of normative social behaviour (TNSB). A representative survey ( n = 1, 001) was conducted measuring consumer behaviour in relation to four single‐use plastic items (bags, straws, coffee cups, and take‐away containers). Descriptive norms were found to be the strongest predictor of plastic avoidance and most of the remaining variables moderated the norm‐behaviour relationship. However, the relative importance of each variable differed depending on the specific item and behaviour. These findings indicate that there is an opportunity to use social norm messaging to close the perception‐action gap among consumers in order to address a global sustainability problem.